Students' Difficulties In Writing Recount Text At The Second Year Of SMP N 2 Kartasura In 2012/2013 Academic Year - Supatmi, Dwi, Drs. Djoko Srijono, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
This study is aimed at describing: 1) the difficulties faced by the students in writing recount text, and 2) teacher's solutions to solve the problems of the students' difficulties of writing recount text. In achieving the objectives, the researcher used descriptive qualitative as an approach to collect and analyze the data. The object of this research is recount text written by the students of SMP N 2 Kartasura in 2012/2013 in academic year. The writer gets the data of the research from the data sources are: English teacher, the students, and the material of recount text written by the students at second year of SMP N 2 Kartasura in 2012/2013 academic year. Techniques of collecting data are document and interview with English teacher. The result of this research is students' difficulties in writing recount text and teacher's solutions for the difficulties faced by the students in writing recount text. The results of students' difficulties are as follows: 1) generic structure, 2) language features. Teacher's solutions for the difficulties are as follows: 1) giving explanation repeatedly to solve generic structure, 2) asking the students to analyzing language features, 3) memorizing past form of word to solve tenses, 4) giving exercise to solve difficulties in grammar and deleting word, 5) looking up at the dictionary to solve difficulties in vocabulary and spelling.